As funções da televisão educativa - Roberto Muylaert - Alves, Januária Cristina (Comunicação & Educação, 1995)
Roberto Muylaert, director of TV Cultura in São Paulo, exposes the philosophy he uses to command the company and shows the distinction that is set up, already in the First World, between Educational TV and TV made in the schools equipped with computers and CD-ROMs. The right thing to do would be to think about an Educational System via satellite, via computer.